Notation Methods and Reference Systems: On the Phenomenon of Cultural Translation in the Eastern Mediterranean - Jäger, Ralf Martin (Oriens, 2023)
Each cultural group has an individual-specific music-theoretical, as well as music-historical background, so that the cultural intersection of Ottoman art music is considered from different perspectives. Using Greek sources from the 18th and 19th centuries as examples, this contribution is devoted to the phenomenon of cultural translation that accompanies the transfer processes. The central question is whether and in what form the detailed information given on the pitch system can contribute to a better understanding of Ottoman music theory in the nineteenth century, and how it can be made useful for the critical edition of music practical sources from the period.